Robotic modelling and simulation: theory and application - Jambak, Muhammad Ikhwan (In-Tech, 2010)
The employment of robots in manufacturing has been a value-adding entity for companies in gaining a competitive advantage. Zomaya (1992) describes some features of robots in industries, which are decreased cost of labour, increased flexibility and versatility, higher precision and productivity, better human working conditions and displaced human working in hazardous and impractical environments. Farrington et al. (1999) states that robotic simulation differs from traditional discrete event simulation (DES) in five ways in terms of its features and capabilities. Robotic simulation covers the visualization of how the robot moves through its environment. Basically, the simulation is based heavily on CAD and graphical visualization tools. Another type of simulation is numerical simulation, which deals with the dynamics, sensing and control of robots. It has been accepted that the major benefit of simulation is reduction in cost and time when designing and proving the system (Robinson, 1996). Robotic simulation is a kinematics simulation tool, whose primary use is as a highly detailed, cell-level validation tool (Farrington et al., 1999), and also for simulating a system whose state changes continuously based on the motion(s) of one or more kinematic devices (Roth, 1999). It is also used as a tool to verify robotic workcell process operations by providing a “mock-up” station of a robots application system, in order to check and evaluate different parameters such as cycle times, object collisions, optimal path, workcell layout and placement of entities in the cell in respect of each other. This paper presents the methodology in modelling and simulating a robot and its environment using Workspace and X3D software. This paper will discuss the development of robotic e-learning to improve the efficiency of the learning process inside and outside the class. This paper is divided into five sections. Section 2 discusses the robotic modelling method. Section 3 discusses robotic simulation. Its application using Workspace and X3D is presented in Section 4, and a conclusion is drawn in Section 5.